Romanesque architecture : The World Architecture - Allsopp, Bruce (The World of architecture.)
A General History Of Architecture AHistory Of Classical Architecture Decoration And Furniture Historic Architecture Of Newcastle upon Tyne Historic Architecture of Northumberland The Great Tradition of Western Architecture